THE ANXIETY OF SOLOMON KANE IN MICHAEL J. BASSET SOLOMON KANE MOVIE (2010): A PSYCHOANALYTIC APPROACH - RACHMAWATI, KARTIKA (2011)
The research is proposed to analyze the anxiety in a film with the title Solomon Kane with Psychoanalytic Approach. There are two objectives: the first is to analyze the film in term of structural elements, and the second is to analyze the film based on Psychoanalytic Approach. This study is a descriptive qualitative study, using the film of Michael J. Bassett Solomon Kane as the subject of analysis of the style study. There are two kinds of data sources use in this analyzing, namely primary and secondary. The primary data are the film and script of the film itself and the secondary data sources are books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. The analysis is started by analyzing Solomon Kane id, ego, superego, and then his anxiety. The last, the writer makes an analysis of Solomon Kane character using anxiety. The outcome of the study shows that the film illustrates the anxiety of Solomon Kane in a hard world in the early sixteenth century. He is a bloodthirsty mercenary who loses his soul to the devil's reaper and then he must save and get redeemed for his soul. Finally, the conclusion of this analysis is that people must be brave to take the consequence of what they choose, in facing the problem they must be able to make up their mind so they will not regret and will reduce their anxiety.